On Blockage Effects for a Tidal Turbine in Free Surface Proximity - Nitin Kolekar (Energies, 2019)
Experiments with a three-bladed, constant chord tidal turbine were undertaken to understand the influence of free surface proximity on blockage effects and near-wake flow field. The turbine was placed at various depths as rotational speeds were varied; thrust and torque data were acquired through a submerged sensor. Blockage effects were quantified in terms of changes in power coefficient and were found to be dependent on tip speed ratio and free surface to blade tip clearance. Flow acceleration near turbine rotation plane was attributed to blockage offered by the rotor, wake, and free surface deformation. In addition, particle image velocimetry was carried out in the turbine near-wake using time- and phase-averaged techniques to understand the mechanism responsible for the variation of power coefficient with rotational speed and free surface proximity. Slower wake propagation for higher rotational velocities and increased asymmetry in the wake with increasing free surface proximity was observed. Improved performance at high rotational speed was attributed to enhanced wake blockage, and performance enhancement with free surface proximity was due to the additional blockage effects caused by the free surface deformation. Proper orthogonal decomposition analysis revealed a downward moving wake for the turbine placed in near free surface proximity.